Medication Errors in Healthcare Systems: A Scoping Review of Causes, Trends, and Technology-Based Prevention Strategies - Tri Sudarwati; Sri Sundari (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Medication errors remain a critical concern in patient safety, significantly affecting the quality of healthcare services. The COVID-19 pandemic further strained global healthcare systems, exacerbating the occurrence of such errors. This study aims to explore publication trends regarding the causes and mitigation strategies of medication errors, with particular emphasis on the use of technology and reporting systems in healthcare settings. A scoping review with a qualitative approach was employed, analyzing literature published between 2019 and 2024. Relevant studies were identified, screened, and systematically analyzed using major scientific databases. The findings indicate a notable increase in publications on medication errors during 2019–2021, primarily driven by heightened stress on healthcare systems amid the pandemic. Frequently reported contributing factors include inadequate training of medical personnel, high workload, ineffective communication among healthcare professionals, and limitations in incident reporting systems. Mitigation strategies increasingly emphasize the implementation of artificial intelligence and electronic reporting systems, which have demonstrated effectiveness in detecting and preventing errors. These results underscore the importance of technology-enhanced interventions and robust reporting mechanisms to improve patient safety. Continued research and implementation efforts are essential to further reduce medication errors and strengthen healthcare quality.